2013
DOI: 10.1080/17441692.2013.810765
|View full text |Cite
|
Sign up to set email alerts
|

Constitutional rights to health, public health and medical care: The status of health protections in 191 countries

Abstract: United Nations (UN) member states have universally recognised the right to health in international agreements, but protection of this right at the national level remains incomplete. This article examines the level and scope of constitutional protection of specific rights to public health and medical care, as well as the broad right to health. We analysed health rights in the constitutions of 191 UN countries in 2007 and 2011. We examined how rights protections varied across the year of constitutional adoption;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 4 publications
0
24
0
Order By: Relevance
“…30 A majority of national constitutions now also guarantee the right to health. 31 Early examples in South Africa and Brazil saw the right to health mobilized to open the floodgates to ARVsand to a burgeoning enforcement movement, led by activists and engaging national courts, to present claims for a right of access to HIV treatment. From Colombia to Kenya to India, courts in just the last few years have ordered policy overhauls to ensure access to medications; in countries like Brazil and Costa Rica, tens of thousands of individual suits are filed each year for access.…”
Section: Elements Of a Human-rights Based Response To New Arv Sciencementioning
confidence: 99%
“…30 A majority of national constitutions now also guarantee the right to health. 31 Early examples in South Africa and Brazil saw the right to health mobilized to open the floodgates to ARVsand to a burgeoning enforcement movement, led by activists and engaging national courts, to present claims for a right of access to HIV treatment. From Colombia to Kenya to India, courts in just the last few years have ordered policy overhauls to ensure access to medications; in countries like Brazil and Costa Rica, tens of thousands of individual suits are filed each year for access.…”
Section: Elements Of a Human-rights Based Response To New Arv Sciencementioning
confidence: 99%
“…After all, the States themselves make a sovereign decision to be bound by human rights treaties, to submit to control mechanisms and to accept various soft law documents. It is noteworthy that although a review of the constitution of 191 countries in the world revealed that the basic laws of 86 countries (45%) lacked any reference to the right to health and health care (Heymann et al 2013), as many as 165 countries were involved in the International Covenant on Economic, Social and Cultural Rights (ICESCR) commitment (Article 12) to ensure ‘the enjoyment of the highest attainable standard of physical and mental health’ (United Nations 1966 a ). According to the principle of pacta sunt servanda – an international customary norm and the Vienna Convention on the Law of Treaties (United Nations 1969), States are obliged to respect the rule that ‘every treaty in force is binding upon the parties to it and must be performed by them in good faith’ (Article 26) and ‘a party may not invoke the provisions of its internal law as justification for its failure to perform a treaty’ (Article 27).…”
Section: Introductionmentioning
confidence: 99%
“…Today, more than 100 national constitutions articulate a right to health-including all but one of 33 constitutions adopted from 2000 through 2011 [25], often following powerful civil society advocacy. Indeed, the right to health has inspired and galvanized civil society.…”
Section: The Right To Health As a Foundation Of Global Health With Jumentioning
confidence: 99%
“…Yet most states have made significant, though incomplete, progress in implementing the treaty [72]. Human rights legal obligations have been widely incorporated into national constitutions [25] and adjudicated through domestic courts, and have empowered civil society advocacy.…”
Section: The Enduring Problem Of Compliance and Enforcementmentioning
confidence: 99%